2022
DOI: 10.1111/adb.13243
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for low‐risk drinking and relapse in alcohol use disorder: A multimodal analysis

Abstract: This study aims to specify the determinants of low‐risk alcohol drinking and relapse at different time points after detoxification in patients with severe alcohol use disorder (AUD). Fifty‐four patients with AUD and 36 healthy controls (HC) were evaluated early in abstinence (T1). They underwent clinical, neuropsychological and neuroimaging (structural MRI and 18FDG‐PET) investigations. Patients with AUD were subsequently classified as “low‐risk drinkers” (LR) or “relapsers” (R) based on their alcohol drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Some studies reported reduced global brain metabolism and especially a hypometabolism in the frontal cortical regions of persons with AD, compared to HCs [174, 175]. Interestingly, Maillard et al [176] found a hypermetabolism in the cerebellum and hippocampus of persons with AD who relapsed within 6 months and additionally in the anterior cingulate cortex of persons with AD who relapsed after 12 months. Further (preclinical) multimodal studies combining PET and MRI in AD investigated glutamatergic but not DA neurotransmission in animal models [177, 178].…”
Section: Correlations With Other Imaging Results (Fmri Mrs)mentioning
confidence: 99%
“…Some studies reported reduced global brain metabolism and especially a hypometabolism in the frontal cortical regions of persons with AD, compared to HCs [174, 175]. Interestingly, Maillard et al [176] found a hypermetabolism in the cerebellum and hippocampus of persons with AD who relapsed within 6 months and additionally in the anterior cingulate cortex of persons with AD who relapsed after 12 months. Further (preclinical) multimodal studies combining PET and MRI in AD investigated glutamatergic but not DA neurotransmission in animal models [177, 178].…”
Section: Correlations With Other Imaging Results (Fmri Mrs)mentioning
confidence: 99%
“…Noteworthy, participants were seen in the context of a large protocol, from which prior results have been published 32–38 …”
Section: Methodsmentioning
confidence: 99%
“…The ability to make flexible decisions is substantially altered by chronic ethanol (EtOH) use and dependence across species, impairing goal-directed behavior while enhancing habitual or stimulus-oriented behavior [1][2][3][4][5][6][7] . Low cognitive flexibility may contribute to future escalation of substance use [8][9][10] , including EtOH intake in both rodents and primates [11][12][13][14] , and in heightening the risk of relapse to alcohol use in humans 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, neural signals in the DMS related to the decision outcome were enhanced, while those related to choice and choice-outcome conjunction were reduced, in EtOH-treated rats compared to the controls. These findings highlight the profound impact of chronic EtOH exposure on adaptive decision-making, pinpointing specific changes in striatal representations of actions and outcomes as underlying mechanisms for cognitive deficits.Cheng et al Page 3 10 , including EtOH intake in both rodents and primates [11][12][13][14] and in heightening the risk of relapse to alcohol use in humans 15,16 .Cognitive flexibility, evaluated through reversal learning tasks 17,18 , involves learning beneficial choice and adapting to new action-outcome contingencies. Although the cognitive and neural mechanisms underlying chronic EtOH-induced reversal deficits are not yet fully understood, studies in humans have shown persistent disruption of reversal learning during protracted withdrawal from EtOH drinking [19][20][21][22] .…”
mentioning
confidence: 99%
See 1 more Smart Citation